2015
DOI: 10.21273/horttech.25.3.349
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous 1-Methylcyclopropene to Delay Ripening of ‘Kent’ Mango With or Without Quarantine Hot Water Treatment

Abstract: Gaseous 1-methylcyclopropene (1-MCP) delays mango (Mangifera indica) fruit ripening, but requires 12 hours of application in sealed containers. In some fruit species, aqueous formulation applied as a postharvest dip for only 1 to 5 minutes has shown the same effectiveness as gaseous 1-MCP. This research was conducted to determine the effectiveness of aqueous 1-MCP on delay of the ripening process, extension of shelf life, and maintenance of fruit quality of ‘Kent’ mango fruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Ripening in mango fruit is characterized by an increase in total soluble solids (TSS) and a decrease in titratable acidity. Previous research revealed that 1-MCP (652 µg L −1 for 5 minutes) reduced the accumulation of TSS in 'Kent' mangoes stored at 12°C (Osuna-Garcia et al, 2015); however, contrasting results have been observed in other varieties (Table 2). Further studies of 1-MCP (1 µL L −1 ) treatment of 'Carabao' mangoes stored at 5°C showed an increase in TSS content (Castillo-Israel et al, 2015).…”
Section: -Methylcyclopropenementioning
confidence: 87%
See 1 more Smart Citation
“…Ripening in mango fruit is characterized by an increase in total soluble solids (TSS) and a decrease in titratable acidity. Previous research revealed that 1-MCP (652 µg L −1 for 5 minutes) reduced the accumulation of TSS in 'Kent' mangoes stored at 12°C (Osuna-Garcia et al, 2015); however, contrasting results have been observed in other varieties (Table 2). Further studies of 1-MCP (1 µL L −1 ) treatment of 'Carabao' mangoes stored at 5°C showed an increase in TSS content (Castillo-Israel et al, 2015).…”
Section: -Methylcyclopropenementioning
confidence: 87%
“…Mechanical damage and poor quality has been reported following heat treatment. For instance, Osuna-Garcia et al (2015) observed lenticel damage and dark browning spots in 'Kent' mango treated with 46.1°C for 90 minutes. Increasing the temperature or exposure time can cause heat-induced injury, firmness, and weight loss leading to rapid fruit decay.…”
Section: Hot Air Treatmentmentioning
confidence: 99%
“…We need also to consider that MG tomatoes are in system‐1 ethylene synthesis, whereas BT fruit have switched to the autocatalytic system‐2 43 ; consequently, it is reasonable to expect that there must be a substantial difference in the wound response between MG and BT tomatoes. Even though we did not evaluate ethylene production in this experiment, an ethylene‐mediated response is essential for the manifestation of a beneficial effect of the HW treatment; for example, Osuna‐García et al 44 . reported that blocking the ethylene receptor with 1‐MCP and subsequently applying HW treatment at 46.1 °C for 90 min in mangoes produced a greater incidence of physiological HW injury with poor visual appearance compared to fruit treated with HW without 1‐MCP.…”
Section: Discussionmentioning
confidence: 99%
“…1-MCP is a useful reagent in commercial use for controlling the ripening process of tropical fruits while maintaining their properties and prolonging shelf-life (Ntsoane et al, 2019). A previous study showed that 1-MCP could maintain the firmness and color and delay the sugar biosynthesis during ripening for up to 3 weeks of transportation followed by more than 1 week in the commercialization phase (Osuna-García et al, 2017). 1-MCP was reported to suppress anthracnose-induced fruit damage and reduce the rotting rate of mango fruit.…”
Section: Synthetic Reagentsmentioning
confidence: 99%